Eugenol: A novel therapeutic agent for the inhibition of Candida species infection - Didehdar, Mojtaba; Chegini, Zahra; Shariati, Aref (Frontiers in Pharmacology, 2022)
The high occurrence and mortality rates related to Candidiasis emphasize the urgent need to introduce new therapeutic approaches to treat this infection. Eugenol, the main phenolic component of Clove and Cinnamomum essential oil, has been used to inhibit growth and different virulence factors of the Candida, including strains with decreased susceptibility to antifungals, particularly fluconazole. The result showed that this compound could bind on the Candida membrane and decrease the ergosterol biosynthesis, consequently leading to the cell wall and membrane damages. Additionally, eugenol not only reduces germ tube formation, which reduces nutrient absorption from host tissues, but it also increases the level of lipid peroxidation and reactive oxygen species, which induces oxidative stress and causes high permeability in the fungal cell membrane. Eugenol inhibited Candida cells' adhesion capacity; additionally, this compound inhibited the formation of biofilms and eliminated established Candida biofilms on a variety of surfaces. Furthermore, eugenol disruption of fungal cell integrity could boost the entry of the antifungal drug into the Candida cell, improving the treatment efficacy. Therefore, eugenol could be applicable in the clinical management of various presentations of Candidiasis, especially mucocutaneous presentations such as oral and vulvovaginal presentation. However, further investigations, including in vivo and animal studies, toxicology investigations, clinical tri¬als as well as molecular analysis, are needed to improve formulations and develop a novel antifungal agent based on eugenol.